Sugar malabsorption in healthy neonates estimated by breath hydrogen. Issue 7 (July 1980) - Douwes, A C; Oosterkamp, R F; Fernandes, J; Los, T; Jongbloed, A A
Abstract : Carbohydrate malabsorption in 110 healthy, term neonates was studied by estimating expired hydrogen (H2) before and after a feed on day 6 or 7. Carbohydrate malabsorption was assumed to be present if the infant excreted > 20 parts per million (ppm) H2. The frequency of carbohydrate malabsorption in 49 breast-fed infants was 25% (n = 12), in 35 infants fed a 7.5% lactose formula it was 31% (n = 11), in 26 infants fed a formula containing 1% lactose and 7.3% maltodextrin it was 15% (n = 4). These differences in frequency were not significant. Peak H2 concentration of the malabsorbers in each group, indicating the degree of carbohydrate malabsorption, was 64, 52, and 32 ppm respectively. The degree of carbohydrate malabsorption did not differ significantly between the breast-fed and the high lactose formula groups, but both groups differed from the low lactose group. H2 excretion was studied for 5 months in an exclusively breast-fed infant. In the first 2 months high concentrations were found and the infant produced 3-5 stools a day. In the next 3 months however, most H2 estimations were normal and only 1-2 stools a week were passed. With the introduction of solids, daily bowel movements promptly reoccurred. Frequency of carbohydrate malabsorption in newborn infants is fairly high and is primarily related to the lactose intake. The frequency and degree of carbohydrate malabsorption were comparable in breast-fed infants and in infants fed on a high lactose formula; this differs from results previously reported.